Cruzando os caminhos do passado: história, sociedade e literatura na participação de Goiás na guerra do Paraguai - Souza Filho, José Atanásio de (2018)
This work was basing on questions about the history of the involvement of the Goian population in Paraguayan War context between 1865 and 1867. In the context of this circumstance are the hypothetical elements of the meaning of the participation of the province of Goias in the largest belligerent conflict in South America in nineteenth century. As an interpretative prerogative, we seek to understand the political and social articulations within the scope of the contribution of the Goian population to the appeals of the imperial government, after decree 3371 of January 7, 1865; we read this contribution as the tribute of Goian blood. The research plan, therefore, took as a parameter the documentary base that represents the information substrate of the war event in the province of Goiás. In this aspect, two realities were configured in the litigation of social events and military logistics in Goian territory: the first, the organization of a military force in aid to the command of the Brazilian expeditionary forces, organized from the provinces of São Paulo and Minas Gerais; the second is that the province of Goiás was motivated to develop agricultural and pastoral production for the purpose of maintaining food for the Brazilian army when it entered Goiás territory. This fact occurred in the second half of 1865. Once this demand was established, our analytical objective was extended to aspects of the materiality of political-administrative actions during the first three years of the war. Our analytical focus turned exclusively to the effects of the Paraguayan War on what represents its offensive presence in the southern territory of the province of Mato Grosso. Our historiographical operation sought the official records and the public representations by means of press and the news of the war subjects in Goiás and of other provinces, mainly of the press of Rio de Janeiro, where the influence of the institutions of the general government in that local media was concentrated. Thus, through forms of speeches about the war event, both in the intellectual, artistic and political manifestations in the press, we contribute in the novel Volunteers, published as a leaflet in the newspaper of Goiás, The Free Tribune between the years of 1880 and 1881. Authored by the second lieutenant of the 20th Goiano Infantry Battalion, Manoel Cavalcante de Albuquerque, who proposed to the literary project of that period to commemorate with that novel the 15 year tributes of the march of the first group of volunteers from the country to the theater of war in the southern province of Mato Grosso on May 15, 1865. Our work analyzes historiographically the impact that the war left in Goias, through the records of individual and collective actions, the administrative achievements of governments and poetic and that have become the main substrata of interpretative plausibility, of argumentative veracity, as to the dialogue between his history and literature and of justifiable historiographical opportunity, regarding the subject of the Paraguayan War in Goiás.